HUBUNGAN PENDAMPINGAN SUAMI DENGAN PENURUNAN RASA NYERI PADA IBU BERSALIN DI PMB ASIH DECKY SIDOMUKTI KRAKSAAN KABUPATEN PROBOLINGGO 2019 - Hikmawati, Nova; Irmayanti, Irmayanti (STIKes Maharani Malang, 2020)
Introduction: Childbirth is a natural process that will take place on its own, but human laborat any time is threatened with complications that endanger the mother and the fetus so that it requires supervision of help and services with adequate facilities. One that can reduce maternal pain during childbirth is assistance from a husband or family. The purpose of this study was to determine whether there was a relationship between husband's assistance and a decrease in maternal pain in Asih Decky?s PMB. Metho: This study uses an analytic design with a cross sectional approach, where the data is obtained through a checklist of respondents conducted on 01 to 31 January 2019 with a total of 65 respondents through accidental sampling technique, namely sampling technique by taking available respondents. Data collection includes coding, editing and tabulating, then the data were analyzed using SPSS 16.0 and obtained chi square with significant value p value 0.05. Results and Analysis: and The results showed that 23 respondents (35.38%) were accompanied by a husband who experienced mild pain, while the mother who was not accompanied by a husband who experienced mild pain 1 respondent (1.38%) so that the value of p value (0.000) <? 0 was obtained , 05. The conclusion of the study is that there is a relationship between husband's assistance and a decrease in pain in maternity mothers. Discussion: The suggestion that is proposed is that every mother should always be accompanied by her husband or family.